Anxiety Disorder Of The Main Character In The Woman In The Window By Joe Wright - Anita; Retno Dwigustini; Sulhizah Wulan Sari (CV. Kalimasada Group Profesional, 2023)
Anxiety disorder is a mental disorder in which the sufferer experiences excessive anxiety. The purpose of this research is to analyses and find out the types of anxiety disorder experienced by the main character as well as knowing the factors that cause anxiety disorder, and the stigma of other characters to the main character. This research uses descriptive qualitative methods and the technique of analyzing data uses images and dialogues in the scene of the film. They are several results of this study; (1) The types of anxiety disorder represented in the main character are Agoraphobia, Post-traumatic stress disorder (PTSD), and Social phobia. (2) The factors of her anxiety disorder are deaths of significant other and serious road accidents.(3) The main character got a lot of negative stigma due to the mental disorders that she had experienced in the past, so she was not believed and got hallucinations, and was crazy. This study is important to know the psychological condition of the human being and treat them as good as possible.